Pyomyositis After Chemotherapy for Endometrial Cancer. Issue 7 (1st October 2010) - Singh, Piksi; Chan, Warren; Blomfield, Penelope; McIntosh, Robert
Abstract : Pyomyositis is a rare complication of chemotherapy that is commonly seen in tropical climates and in patients with immunodeficiency states. Owing to its rarity and subacute presentation, its diagnosis is often delayed. It has been reported after intense chemotherapy for hematological cancers. We present a case of a 58-year-old woman with endometrial cancer who developed pyomyositis after the first cycle of carboplatin and paclitaxel with no prior predisposing factor except for cancer and premedication with corticosteroids. The patient improved once the diagnosis was established and managed with antibiotics and drainage of abscess. Full recovery was made with a protracted course of antibiotics. Early diagnosis of this entity with appropriate investigations and treatment prevents septicemia, which can often be life threatening.